Factors associated with empathy among community pharmacists in Lebanon - Eva Hobeika; Souheil Hallit; Hala Sacre; Sahar Obeid; Aline Hajj; Pascale Salameh (Journal of Pharmaceutical Policy and Practice, 2020)
Introduction Empathy is the cornerstone of the relationship between the healthcare provider and the patient. In Lebanon, no studies have investigated the factors associated with empathy among community pharmacists. Hence, the importance of this research to better understand empathy and help community pharmacists with this vital aspect of their practice. Objective This study aimed to evaluate empathy and possible factors associated with it among Lebanese community pharmacists. Methods This cross-sectional study was carried out between March and July 2018. It enrolled a proportionate random sample of 435 community pharmacists from all Lebanese districts. The Epi info software calculated the minimum sample size, based on a total number of 3762 community pharmacists, with an expected frequency of 50% of pharmacists with low empathy, and a 95% confidence interval. The minimal sample size required was 350 community pharmacists; our sample size was 435 to account for missing values. Results Our results revealed that 228 (53.4%) pharmacists had low empathy. Lower empathy was significantly associated with more physical (Beta = − 0.331) and mental (Beta = − 0.126) work fatigue, higher age (Beta = − 0.125) and a practice experience between 3 years and less than 6 years compared to less than 6 months (Beta = − 2.440). Conclusion This study shed the light on some factors associated with empathy among Lebanese community pharmacists. Low empathy levels were significantly associated with factors such as age, practice experience, and mental and physical work fatigue, all of which impact the practice, as the accepted model of pharmacy practice requires that pharmacists establish effective communication and use interpersonal skills. Therefore, developing empathetic communication skills is considered essential. Furthermore, increased mental and physical work fatigue should not hinder community pharmacists’ access to self-care, whether for their mental or physical health.